Extracellular vesicle microRNA in early versus late pregnancy with birth outcomes in the MADRES study - Caitlin G Howe; Helen B Foley; Elizabeth M Kennedy; Sandrah P Eckel; Thomas a Chavez; Dema Faham; Brendan H Grubbs; Laila Al-Marayati; Deborah Lerner; Shakira Suglia; Theresa M Bastain; Carmen J Marsit; et al. (Epigenetics, 2022)
Circulating miRNA may contribute to the development of adverse birth outcomes. However, few studies have investigated extracellular vesicle (EV) miRNA, which play important roles in intercellular communication, or compared miRNA at multiple time points in pregnancy. In the current study, 800 miRNA were profiled for EVs from maternal plasma collected in early (median: 12.5 weeks) and late (median: 31.8 weeks) pregnancy from 156 participants in the MADRES Study, a health disparity pregnancy cohort. Associations between miRNA and birth weight, birth weight for gestational age (GA), and GA at birth were examined using covariate-adjusted robust linear regression. Differences by infant sex and maternal BMI were also investigated. Late pregnancy measures of 13 miRNA were associated with GA at birth (PFDR<0.050). Negative associations were observed for eight miRNA (miR-4454+ miR-7975, miR-4516, let-7b-5p, miR-126-3p, miR-29b-3p, miR-15a-5p, miR-15b-5p, miR-19b-3p) and positive associations for five miRNA (miR-212-3p, miR-584-5p, miR-608, miR-210-3p, miR-188-5p). Predicted target genes were enriched (PFDR<0.050) in pathways involved in organogenesis and placental development. An additional miRNA (miR-107), measured in late pregnancy, was positively associated with GA at birth in infants born to obese women (PFDR for BMI interaction = 0.011). In primary analyses, the associations between early pregnancy miRNA and birth outcomes were not statistically significant (PFDR≥0.05). However, sex-specific associations were observed for early pregnancy measures of 37 miRNA and GA at birth (PFDR for interactions<0.050). None of the miRNA were associated with fetal growth measures (PFDR≥0.050). Our findings suggest that EV miRNA in both early and late pregnancy may influence gestational duration.